2020
DOI: 10.1002/jcb.29617
|View full text |Cite
|
Sign up to set email alerts
|

A novel miRNA located in the GATA4 gene regulates the expression of IGF‐1R and AKT1/2 genes and controls cell proliferation

Abstract: GATA4 gene is a zinc-finger transcription factor known to be involved in cardiogenesis and the progression of different cancer types. Its diverse functions might be attributed to noncoding RNAs that could be embedded within its sequence.Here, we predicted a stable RNA stem-loop structure that is located in the second intron of the GATA4 gene. Available microRNA (miRNA) sequencing data and molecular genetics tools confirmed the identity of a mature miRNA (named GATA4-miR1) originating from the predicted stem-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, a luciferase reporter assay documented a direct interaction between this miRNA and the target genes. GATA4-miR1 overexpression in the CRC cell line determined an increase in the sub-G1 cell cycle population, and a reduction in cell survival and proliferation (96). This newly discovered miRNA warrants further investigation in particular within the context of cell cycle progression and cell proliferation in order to establish whether it could have a therapeutic potential in CRC.…”
Section: Mirnas Regulating the Gh/igf1 Axis And Igf System In Colorectal Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, a luciferase reporter assay documented a direct interaction between this miRNA and the target genes. GATA4-miR1 overexpression in the CRC cell line determined an increase in the sub-G1 cell cycle population, and a reduction in cell survival and proliferation (96). This newly discovered miRNA warrants further investigation in particular within the context of cell cycle progression and cell proliferation in order to establish whether it could have a therapeutic potential in CRC.…”
Section: Mirnas Regulating the Gh/igf1 Axis And Igf System In Colorectal Cancermentioning
confidence: 91%
“…The newly discovered GATA4-miR1 was located in the second intron of the GATA4 gene, which belongs to a transcription factor family involved in carcinogenesis (96). Bioinformatic tools and experimental research identified IGF1R, AKT1 and AKT2 genes as GATA4-miR1 targets.…”
Section: Mirnas Regulating the Gh/igf1 Axis And Igf System In Colorectal Cancermentioning
confidence: 99%